2006
DOI: 10.2527/jas.2006-176
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci affecting corpora lutea and number of teats in a Meishan × Duroc F2 resource population

Abstract: Understanding of the genetic control of female reproductive performance in pigs would offer the opportunity to utilize natural variation and improve selective breeding programs through marker-assisted selection. The Chinese Meishan is one of the most prolific pig breeds known, farrowing 3 to 5 more viable piglets per litter than Western breeds. This difference in prolificacy is attributed to the Meishan's superior prenatal survival. Our study utilized a 3-generation resource population, in which the founder gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 17 publications
5
34
1
Order By: Relevance
“…Although many studies have found a QTL for NTE on SSC12 [9, 11, 12, 17, 18], only Guo et al [12] found a large QTL interval similar to ours in an F2 cross between Large White and Chinese Meishan. Within this region, we find the δ- EF1 gene is of particular interest because its expression in the somites [58] may suggest a role in vertebrae and mammary development in a mechanism similar to Vertnin , as described above.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although many studies have found a QTL for NTE on SSC12 [9, 11, 12, 17, 18], only Guo et al [12] found a large QTL interval similar to ours in an F2 cross between Large White and Chinese Meishan. Within this region, we find the δ- EF1 gene is of particular interest because its expression in the somites [58] may suggest a role in vertebrae and mammary development in a mechanism similar to Vertnin , as described above.…”
Section: Discussionsupporting
confidence: 82%
“…The QTL which explains the most genetic variation is located on SSC7 and has been identified in other studies [9, 11, 12, 17, 18]. While Mikawa et al [48] reported an additive effect of this QTL on number of vertebrae, we observed a dominant or even overdominant effect on the number of teats in our population.…”
Section: Discussionsupporting
confidence: 62%
“…In mammals in particular, imprinted genes have an important effect in the regulation of fetal growth, development, function of the placenta, and postnatal behavior (Isles and Holland, 2005). In pigs, many imprinted quantitative trait locus (QTL) significantly affect growth, backfat thickness, carcass composition and reproduction (de Koning et al, 2000;Sato et al, 2006;Ding et al, 2009;Uemoto et al, 2009;Ruckert and Bennewitz, 2010). The IGF2 gene, which was identified as the first imprinted gene in pigs, has important effects on porcine growth, meat quality and carcass composition, especially on fat deposition (Estellé et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative trait loci (QTL) for teat traits on chromosome 8 have been identified by several authors (Cassady et al, 2001;Beeckmann et al, 2003;Sato et al, 2006). LEF1 was displayed in close proximity to these QTL and thus is a positional candidate gene.…”
Section: Discussionmentioning
confidence: 99%